Primary and secondary dentine thickness at the apical foramen of the mesial and distal root of the lower first permanent molar - Jovanović-Medojević Milica (Stomatološki glasnik Srbije, 2009)
Introduction Knowledge of the complexity of the root canal system in lower first molars and particularly the apical part of the root affects significantly the realization and success of the endodontic procedure. Aim The aim of this paper was to determine the thickness of the primary and secondary dentine around the main foramen of the mesial and distal root of the lower first permanent molar in teeth of various ages. Material and Method Fifty extracted lower first molars of both male and female patients extracted for various reasons were used in the study. All teeth were allocated to three age groups: under 25 years old (15 teeth), between 26 and 50 (20 teeth) and over 51 years old (15 teeth). After access cavity preparation, canal orifices were enlarged and root canals were explored using hand K-files #10. Using a diamond disc, the root tip was then cut off in the area of the apical foramen. Dentine thickness was determined using a complex configuration comprising of several devices which were interconnected by software. These included a polarised microscope (Leica DMLSP), a digital camera (Leica DC300) and a scanner. Results The results showed that the greatest mean thickness of the primary dentine was in the mesial root of the first lower molar in the first age group (0.177 mm), followed by the third (0.145 mm) whilst the least mean thickness was observed in the second age group (0.141 mm). In the distal root, the mean thickness of the primary dentine was in the second (0.175 mm), then the first (0.138 mm) and finally the third group (0.100 mm). The mean thickness of the secondary dentine in the mesial root was observed in the second group (1.25 mm), followed by the third (1.11 mm) whilst the least mean thickness was found in the first age group (0.95 mm). The mean thickness of the secondary dentine in the distal root was observed in the second group (1.26 mm), then the third (1.18 mm) whilst the least mean thickness was found in the first age group (0.99 mm). Conclusion The obtained results suggested that the mean thickness of the primary dentine in the mesial and distal roots was comparable. For both mesial and distal roots, the greatest mean thickness of the secondary dentine was observed in the second age group.